Acute pain problems post surgery carcinoma mammary : a case study - Mardiah Mardiah (Institute Of Computer Science (IOCS), 2023)
Carcinoma mammae or breast cancer is a disorder in irregular cell growth that becomes a lump that grows in the duct that connects the lobolus to the nipple. The purpose of the case study was to do Nursing Care for Mrs.